Music performance anxiety in adolescent student singers : a thesis submitted to the Victoria University of Wellington in fulfilment of the requirements for the degree of Master of Music [in Performance] - Corby, Megan (New Zealand School of Music, 2008)
This project seeks to sidestep the debilitating effects of music performance anxiety by cross-referencing knowledge from the areas of adolescent psychology with literature on MPA in singers in general in order to target adolescent singers early in their training. As well as considering the causes, symptoms and treatment of music performance anxiety, the project examines the role of the natural anxieties of adolescence in triggering music performance anxiety and seeks to chart a way through. Its intended readership is the classical singing teacher.
Keywords: Music; Performance anxiety; Adolescents; Singers; Fields of Research::410000 The Arts::410100 Performing Arts Studies::410101 Music studies